The complete chloroplast genome sequence of Nicotiana debneyi (Solanaceae). Issue 3 (4th March 2021) - Zeng, Jianmin; Huang, Changjun; Liu, Yong; Yuan, Cheng; Yu, Haiqin; Song, Biqing
Abstract: In present study, we report the complete chloroplast genome of Nicotiana debneyi, a species endemic to eastern coast of Australia. The total genome size of N.debneyi is 156, 073 bp in length, containing a large single-copy region of 86, 672 bp, a small single-copy region of 18, 581 bp, and two inverted repeat regions of 25, 410 bp. The all GC content of N.debneyi chloroplast genome is 38.4%. It encodes a total of 129 unique genes, including 84 protein-coding genes, 37 tRNA genes, and eight rRNA genes, of which seven tRNA, four rRNA and seven protein-coding genes are duplicated in the IR. Sixteen genes contain a single intron, and only two genes have two introns. Phylogenetic analysis results strongly supported that N.debneyi was closely related to Nicotiana sylvestris and Nicotiana tabacum .